Performance Analysis of a Solar-Powered DC System toward Sustainable Cooling and Heating in a Hot Arid Climate: A Madinah Case Study - Alrwishdi, Emad; Al Ahmadi, Saleh; Al Kassem, Abdulrahman; Draou, Azeddine (Engineering, Technology & Applied Science Research, 2026)
As global temperatures rise and energy demands intensify, innovative climate-control solutions are essential for sustaining comfort in extreme environments. However, most existing Air-Conditioning (A/C) systems in hot-arid regions still rely on conventional Alternating-Current (AC) power, leading to significant conversion losses and limiting solar integration. This highlights the necessity for efficient, fully Direct-Current (DC)-powered alternatives. This study evaluates the performance and energy efficiency of a variable-speed DC A/C and heating system installed in Madinah, Saudi Arabia, during the summer of 2024 (June, July, August) and the winter of 2025 (January). The experimental investigation analyzes cooling and heating capacities, power consumption, ambient and indoor temperatures, and the Coefficient of Performance (COP). The system maintained an average indoor temperature of approximately 24 °C in summer and 25 °C in winter, ensuring thermal comfort despite outdoor temperatures exceeding 45 °C in summer and dropping to around 10 °C in winter. The peak cooling capacity reached 2261.4 W in July, accompanied by a 3% increase in total energy consumption compared to June. The highest cooling COP of 3.08 was recorded in June. This value decreased to 2.81 in July and recovered to 2.91 in August. During winter heating operation, the system achieved a COP of 5.72, delivering 10.19 kWh of heat with minimal energy input and demonstrating strong seasonal performance. The variable-speed operation enabled efficient adaptation to fluctuating conditions, confirming its suitability for extreme climates. The findings encourage future optimization through improved insulation, advanced control strategies, and renewable energy integration to enhance overall efficiency and promote sustainable building technologies.